Business Impact Analysis Implementation Within Business Continuity Management Framework at PT Adhya Tirta Batam - Ariyanto, Roni Hartawan; Susilo, Leo J (The Indonesian Journal of Business Administration, 2014)
Abstract - Potential risks such as power outages, natural disasters, fires, and other crisis automatically impact water utilities. Considering these potential risks, ATBâ€™s top management had decided to conduct a critical evaluation about the capability of the company and thoroughly address how they will keep their utility in operations and business during and after disasters. They need to identify and assess the potential business impact whether these activities are interrupted over varying timeframes, determine the timeframes within which critical business activities must be resumed following an emergency or disaster, and identifying resources that are required to support these activities for Business Continuity purposes through the implementation of Business Impact Analysis (BIA) as foundation for Business Continuity Management (BCM) implementation. BIA objectives are to determine: (a) corporate and departments Minimum Business Continuity Objective (MBCO) during disaster situation, (b) critical department within ATB organization during emergency event, (c) critical processes during emergency event, and (d) minimum human and physical resources to be allocated to recover and resume the department in the event of disaster. Results of BIA indicate that recovery process after disaster in ATB should be started within 4 hours with Production and Distribution departments as first group to start their recovery to supply 30 liter per person per day per corporate MBCO. From total 13 departments were identified 2 departments as critical process, 9 departments as important units and 2 departments as non-critical units. To perform such processes, ATB needs minimum 224 peoples from existing staffs to support critical processes in the event of disasters. Â Keyword: Business Impact Analysis, Business Impact Analysis Questionnaire, Business Continuity Management, Minimum Business Continuity Objective.